Cardiac Lipoma at Unusual Location – Mimicking Atrial Myxoma. Issue 3 (11th January 2013) - Singh, Bhupinder; Bhairappa, Shivakumar; Shankar, Subramani Khamitkar; Prasad, N. M.; Manjunath, C. N.
<x xml:space="preserve">Abstract</x> Cardiac lipomas are one of the rare primary benign neoplasms composed of mature fat cells. The tumor originates mostly in the subendocardium and subepicardium but very rarely within the myocardium. Clinically, this tumor is asymptomatic and found incidentally in the vast majority of cases. We report a 26‐year‐old female presenting with atypical chest pain. Transthoracic echocardiogram showed a mass in relation to interatrial septum suggestive of atrial myxoma, but was confirmed to be cardiac lipoma on magnetic resonance imaging. Owing to the asymptomatic character and the benign nature of the tumor, a decision for conservative management was made.